On Observation of Slow Ultrasonic Waves in Cancellous Bones - Kubik, J.; Kaczmarek, M.; Pakuła, M. (Engineering Transactions, 2001)
The two-phase model of saturated cancellous bones predicts the existence of two longitudinal waves in the materials. The paper disscusses experimental results concerning ultrasonic studies of the slow longitudinal wave. Results available in the literature are reviewed and compared with author's data obtained through broadband ultrasonic spectroscopy. The essential properties of the measured slow wave as well as technical and material difficulties in interpretation of the data are highlighted.